KOALISI PARTAI POLITIK DALAM PEMENANGAN PASANGAN INDRA PUTRA DAN KOMPERENSI PADA PEMILIHAN KEPALA DAERAH DI KABUPATEN KUANTAN SINGINGI 2015 - Syafitri Yona Sari; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of research are ;1) to know how political coalition make good relationship among the other parties on regency election in kuantan singingi regency 2015. 2) to know wh the coalition parties getting lost in regency election in Kuatan Singingi 2015This research has conducted in kuantan singingi regency as long away 6 months. The method of the research was doing by qualitative. The data was using primer and secondary data. Primer data form have shape of interview and research location. While, Secondary data form are docmentation and publication. The research showed;1) that first one purpose of the esearch has discribed that coalition of Indra putra- komperensi partner had been made no good relationship between individu and parties . 2) the second of purpose this research are that quick count electric showed that Mursini – Halim partner has been hight score of other partner ( Indra Putra- Komperensi and Mardjan Ustha- Muslim). Quarrel of superiority of Mursini- Halim on Indra Putra quite slight is 389 voted.Keywords: Coalition, Election, politic Parties